Do digital hugs work? Re-embodying our social lives online with digital tact - James, Mark M.; Leader, John Francis (Frontiers in Psychology, 2023)
The COVID-19 pandemic led to social restrictions that often prevented us from hugging the ones we love. This absence helped some realise just how important these interactions are to our sense of care and connection. Many turned to digitally mediated social interactions to address these absences, but often unsatisfactorily. Some theorists might blame this on the disembodied character of our digital spaces, e.g., that interpersonal touch is excluded from our lives online. However, others continued to find care and connection in their digitally mediated interactions despite not being able to touch. Inspired by such contrasting cases, we ask if 'digital hugs' can work? We use the Mixed Reality Interaction Matrix to examine hugging as a social practice. This leads us to several claims about the nature of our embodied social interactions and their digital mediation: 1) all social interaction is mediated; 2) all virtual experiences are embodied; 3) technology has become richer and more supportive of embodiment; and 4) expertise plays a role. These claims help make the case that quality social connections online are substantially dependent upon the dynamic skilful resourcing of multiple mediating components, what we term digital tact. By introducing and developing this concept, we hope to contribute to a better understanding of our digital embodied sociality and the possibilities for caring connections online.